Environmental enrichment as positive welfare of pigs: a review - Maia, Ana Paula de Assis; Sarubbi, Juliana; Medeiros, Brenda Batista Lemos; Moura, Daniella Jorge de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/2236117010746 The competitiveness of Brazilian pig production in the world market depends on their adaptation to global trends and technologies. Animal welfare as a requirement of international markets has generated discussion and questions about the current Brazilian pig farming. The intensive pig farming raises the most serious welfare concerns once it is surrounded by stress factors. Thus, environmental enrichment plays an important role as a simple and effective tool that can ensure the welfare of captive animal. Enrich an environment enhance the physical and psychological health by providing environmental stimuli necessary for encouraging the expression of natural inherent behaviors. Several stimuli which incite an animal´s interest in a positive way can be used to enrich the housing systems, such as offering toys and substrate. This paper reviews the literature concerning environmental enrichment for pigs’ welfare and some methods to enrich the pig housing system.